Cognitive Abilities Related to Reading and Writing Skills in Chinese Third-grade Children - Ou, Jieping; Sambai, Ami; Pei, Hong; Uno, Akira; Yoneda, Hiroki (Journal of ICSAR, 2023)
In this study, we analysed the cognitive abilities that predict reading and writing attainment in the Chinese language for Mandarin-speaking children. A total of 140 Chinese third-graders studying in Ningbo, Zhejiang were evaluated for their visual cognition including visual perception and memory, naming speed, vocabulary knowledge, phonological skills, nonverbal intelligence, and abilities to read and write. The results of multiple regression analyses revealed that word and nonword reading accuracy were predicted to a significant degree by visual memory and phonological awareness, respectively. Naming speed significantly contributed to the reading speeds regarding words, nonwords, and paragraphs. Our results also showed that the scores in word and nonword reading predicted the scores of writing as well. Visual memory and phonological awareness are essential for reading Chinese accurately, while naming speed is an important factor for Chinese reading fluency. The present results have implications regarding the design of useful tasks that screen poor readers of Chinese.